2016
DOI: 10.1177/0959683616678459
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial and aquatic palynomorphs in Holocene sediments from the Chukchi–Alaskan margin, western Arctic Ocean: Implications for the history of marine circulation and climatic environments

Abstract: Two sediment cores from the Chukchi Sea margin north of Alaska were analyzed for palynological composition including terrestrial and aquatic palynomorphs. Based on 13 radiocarbon ages, the investigated sedimentary record represents most of the Holocene with a century to multidecadal age resolution. Three palynological zones were discriminated based on the abundance of major palynomorph groups (terrestrial and freshwater palynomorphs and dinoflagellate cysts) and composition of spore and pollen assemblages. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
(116 reference statements)
1
4
0
1
Order By: Relevance
“…This timing is also consistent with sea-level records from Beringia (Elias et al, 1996;Mason and Jordan, 2002). The coincidence between our age expectation and the well-dated cores by previous studies (Bauch et al, 2001;Kim et al, 2017;Lisé-Pronovost et al, 2009) guarantees a plausible and acceptable age estimate for the lithologic boundary between Unit 2a and Unit 2b, which is indicative of depositional environment changes, although this age postdates a little the timing when the sea level reached the present condition (Figure 2c).…”
Section: Age Estimate Of Core Sedimentssupporting
confidence: 91%
See 2 more Smart Citations
“…This timing is also consistent with sea-level records from Beringia (Elias et al, 1996;Mason and Jordan, 2002). The coincidence between our age expectation and the well-dated cores by previous studies (Bauch et al, 2001;Kim et al, 2017;Lisé-Pronovost et al, 2009) guarantees a plausible and acceptable age estimate for the lithologic boundary between Unit 2a and Unit 2b, which is indicative of depositional environment changes, although this age postdates a little the timing when the sea level reached the present condition (Figure 2c).…”
Section: Age Estimate Of Core Sedimentssupporting
confidence: 91%
“…A little older age is a result that this shell fragment is reworked. In addition, Kim et al (2017) divided three palynological zones from a core (ARA02B-01A) collected in the northern margin of Chukchi Shelf and, conclusively, their lower lithologic boundary (~8400 cal. yr BP) is matched thoroughly with the age estimate between Unit 1 and Unit 2a.…”
Section: Age Estimate Of Core Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various stratigraphic and sedimentological data on one or several of the cores under study have been reported in a number of papers (Barletta et al, 2008;McKay et al, 2008;Darby et al, , 2012Polyak et al, 2009Polyak et al, , 2016Lisé-Pronovost et al, 2009;Faux et al, 2011;Kim et al, 2016). Sediments in cores 08JPC and 01A-GC consist predominantly of homogenous clayey silts indicative of open-marine environments, with a more sandy composition near the core bottom, possibly related to shallow-water erosion and redeposition during the shelf flooding .…”
Section: Samples and Age Constraintsmentioning
confidence: 95%
“…Для палинологического анализа использовались образцы объемом 1 см 3 . По методике [Rudaya, 2010;Kim et al, 2017] были добавлены две таблетки с калиброванным маркером (споры Lycopodium), необходимым для подсчета концентрации зерен. Пробы заливались 10%-ной HCl для удаления карбонатов, затем органическая часть осадка, содержащая пыльцу и споры, отделялась кипячением в 10%-ном растворе KOH с последующей сепарацией в тяжелой жидкости KJ+KdJ (удельный вес -2.2 г/см 3 ).…”
Section: методы исследованияunclassified